Some experiences in adapting previously free-ranging traditionally managed Matabele goats of Zimbabwe to individual stall-feeding - Sibanda, Lindiwe Majele; Ndlovu, L.R.; Bryant, M.J. (1992)
One hundred multiparous indigenous does were purchased from communal farmers for on-station trials. At the research site, the goats were confined and zero-grazed. During adaptation, six goats died, 28 aborted, 56 kidded and 10 had no reproduction records. The does lost weight and were afflicted by diseases not previously experienced under the traditional management system. After nine months of adaptation to the station regime, the goats were synchronised for oestrous and mated. Only 74% of the flock conceived and kidded while 19% did not conceive and 7% aborted. Factors considered to be associated with the poor adaptability to stall-feeding of previously free-ranging goats are discussed.